Educational Management in Times of Pandemic: A Panoramic View in Latin America - Mendoza Jimenez, Hilda Rocio (2023)
As a result of a systematic review obtained, eight levels of constructs: educational inequalities, online education, Covid’s impact, educational management, and Covid’s effects, innovator leadership, resilience, home as an adaptation source, and, finally, sustainable actions. The results showed that the pandemic put in evidence a big social gap between educational communities in Latin America where access to the obtention of technological resources to teach-learn process and handle digital competencies in teachers. In addition, it showed many inequalities in people to energy and connectivity access as minimal conditions to do educational activities, meanwhile health restrictions during Covid-19.